Mapping the state of the art on green logistics and institutional pressures: A bibliometric study (2018)
This article aims to build knowledge on the theme “green logistics” and “institutional pressures”, focused on identifying opportunities on its research topic. We used the ProKnow-C intervention instrument, resulting in the selection of 11 relevant articles that came to represent the bibliographic portfolio. Therefore, the bibliometric indicators based on the most prominent journals, the impact factor, the number of citations, the origin of the research centers, the research methods/tools, the most used terms and the subjects covered were used to analyze the articles selected. research in the form of networks. The results showed that the most prominent journal is the International Journal of Production Economics; the article with the largest number of citations (343 citations) is written by Sameer Kumar and Valora Putnam. In relation to the origin of the research centers there was a diversity of institutions of various nationalities, the USA being the country with the largest number of institutions, followed by United Kindon and Malaysia. As for the research methods, we have identified literature reviews, case studies, surveys, conceptual framework proposal and monitoring system development. In relation to the mapping and research networks, we highlight terms such as logistic, regulatory pressure, practice, driver, economic performance, institutional pressure, among other relevant terms. In this context, this information can “shed light” on interested parties and researchers on the subject in order to conceptualize, interpret and visualize their relevance, as well as the coverage networks and related researches